The Role of Left Hemispheric Structures for Emotional Processing as a Monitor of Bodily Reaction and Felt Chill – a Case-Control Functional Imaging Study - Grunkina, Viktoria; Holtz, Katharina; Klepzig, Kai; Neubert, Jörg; Horn, Ulrike; Domin, Martin; Hamm, Alfons O.; Lotze, Martin (Frontiers in Human Neuroscience, 2017)
Background. The particular function of the left anterior human insula on emotional arousal has been illustrated with several case studies. Only after left hemispheric insula lesions, patients lose their pleasure in habits such as listening to joyful music. In functional magnetic resonance imaging studies (fMRI) activation in the left anterior insula has been associated with both processing of emotional valence and arousal. Tight interactions with different areas of the prefrontal cortex are involved in bodily response monitoring and cognitive appraisal of a given stimulus. Therefore, a large left hemispheric lesion including the left insula should impair the bodily response of chill experience (objective chill response) but leave the cognitive aspects of chill processing (subjective chill response) unaffected. Methods. We investigated a patient (MC) with a complete left hemispheric media cerebral artery stroke, testing functional magnetic resonance imaging (fMRI) representation of pleasant (music) and unpleasant (harsh sounds) chill response. Results. Although chill response to both pleasant and unpleasant rated sounds was confirmed verbally at passages also rated as chilling by healthy participants, skin conductance response was almost absent in MC. For a healthy control (HC) objective and subjective chill response was positively associated. Bilateral prefrontal fMRI-response to chill stimuli was sustained in MC whereas insula activation restricted to the right hemisphere. Diffusion imaging together with lesion maps revealed that left lateral tracts were completely damaged but medial prefrontal structures were intact. Conclusions. With this case study we demonstrate how bodily response and cognitive appraisal are differentially participating in the internal monitor of chill response.